Effect of processing parameters on microstructure of laser solid forming Inconel 718 superalloy. (1st January 2018) - Zhu, L.; Xu, Z.F.; Liu, P.; Gu, Y.F.
Highlights: Fine and coarse columnar dendritic microstructure of as-deposited IN718 superalloy are respectively obtained. The influence of the average widths of columnar grains of LSF IN718 superalloy is studied. The tensile microstructure of as-deposited IN718 superalloy is proposed. Abstract: The present work studies the influence of various parameters on the as-deposited Inconel 718 (IN718) superalloy using laser solid forming method. The microstructure and mechanical properties of IN718 superalloys were analysed. Fine and coarse columnar dendritic microstructure of as-deposited IN718 superalloy are respectively obtained at different laser power and laser beam diameter. The average widths of columnar grains of LSF IN718 superalloy enlarge with increasing laser power and laser beam diameter. The formation of Nb and Mo rich Laves phase in the inter-dendritic regions is found. The highest yield strength and ultimate tensile strength is about 729 MPa and 936 MPa, respectively.